KEEFEKTIFAN PENDEKATAN KETERAMPILAN PROSES SAINS BERBANTUAN LEMBAR KERJA SISWA PADA PEMBELAJARAN KIMIA (Universitas Negeri Semarang, 2014)
Science process skills approach needed in effective chemistry learning. This can be done with the help of student learning media such as student worksheets which contribute to the development of students' independence, skills, affective, cognitive, and psychomotor and personal abilities of students and further developed in the group, especially on the practical implementation. This study aims to determine the effectiveness of the chemistry teaching science process skills approach with worksheets assisted that is applied to the teaching process of SMA N in Pemalang. The study design was a pretest and posttest control group. Samples were choosen by cluster random sampling technique, so the experimental class using science process skills approach aided student worksheets while the control class without learning science process skills approach. Data analysis used the left-mean difference test and t-test, cognitive learning outcomes were analyzed with statistical parametric, whereas the affective aspect, psychomotor and science process skills, were analyzed descriptively. The effectiveness of treatment is known from the results of gain test that using student’s pretest and posttest data. The gain results of the analysis of cognitive test is 0.79 for experimental class with a high criterion that indicates the level of understanding students are significantly different (high). The conclusion of this research is science process skills approach aided worksheets effectively to the achievement of student learning outcomes with classical learning completeness 86.09%.Keywords: Learning Effectiveness, Science Process Skills, Student Worksheets